Pelatihan pembuatan Virgin Coconout Oil (VCO) pada Kelompok Tani Kelurahan Tonyamang Kecamatan Patampanua Kabupaten Pinrang - Taty Sulastry; Mohammad Wijaya; Sitti Faika; Munawwarah Munawwarah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Coconut plantations (Cocos nucifera) are one of the leading commodities of estate crops in Pinrang and these plants are more numerous than other plants in community plantations. However, the role of coconut as a raw material for cooking oil, is currently sinking and displaced by the presence of palm oil commodities. Utilization of by-products has not been done much by farmers, so the added value of farming has not been obtained optimally. Even though many processed products from coconut have the potential to provide high added value, as well as in creating jobs. Lately, virgin coconut oil has also developed, namely VCO (Virgin coconut oil) which is a food supplement and also a medicine. Farmer groups in Pinrang district are one of the farmer groups that have problems with coconut income, namely the use of coconuts has not been maximized and its storage capacity is relatively short. To overcome this problem, the community service team from Makassar State University and the coconut farmers group in Pinrang district discussed the process of managing coconut. The target is expected to be achieved after the implementation of whether community service activities through the coconut oil into VCO program will be able to produce VCO with better quantity and quality, so that the maximum results can expand its business by diversifying coconut products into VCO for health. This research was conducted through two stages, namely the provision of material about VCO and its use, and guidance in making VCO. Based on the results obtained, most people understand the VCO material delivered and are able to make the VCO.